Finite Element Calculation and Its Test Study of Flexible Pin Structure in the 3.X MW Wind Turbine Gearbox - Jinku Li; Wei Liu; Liangrong Li (Jixie chuandong)
Taking the flexible pin of planetary gear train of the first stage of 3.X MW wind turbine gearbox as study object， a finite model that considering gear mesh，bearing and bolt preloading is built. The stress and the displacement of the planetary gear train under rated working conditions are analyzed. The clearance change between the elastic pin sleeve and the limited block and the maximum displacement of the pin shaft are calculated. The results show that the clearance of the sleeve and the limited block is decreased 0.285 mm， but not touched， the maxium displacement of flexible pin is 0.24 mm. And the mean load factor （<alternatives>kγ <?fx-imagestate width="2.62466669" height="3.72533321"?> <?fx-imagestate width="2.62466669" height="3.72533321"?> </alternatives>） and the gear trace load distribution factor （<alternatives>KFβ <?fx-imagestate width="4.82600021" height="3.72533321"?> <?fx-imagestate width="4.82600021" height="3.72533321"?> </alternatives>） based on the gear ring root stress distribution are calculated， the mean load test of this 3.XMW wind turbine gearbox is carried out. The comparison results show that， the mean load factor of FE result is well matched to the practical situation， and this flexible pin has a perfect mean load performance.